2020
DOI: 10.1111/tbed.13894
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology investigation of PRRSV discharged by faecal and genetic variation of ORF5

Abstract: Wensvoort et al., 1992). The disease has caused tremendous economic losses in the global swine industry. PRRS virus (PRRSV), a positive single-stranded RNA virus of the order Nidovirales, family Arteriviridae is the aetiologic agent of this disease (Cavanagh, 1997). The viral RNA genome is approximately 15.4 kb in size and consists of at least ten open reading frames (ORFs) (Johnson et al., 2011). ORF1a and ORF1b comprise almost 80% of the viral genome and encode at least 16 non-structural proteins (Nsps) invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…The average age of the infected population is now believed to be lower compared to the pandemic outbreak in March 2020, possibly due to wider RT-PCR availability and the consequent reduction in missed diagnoses, especially in mild and asymptomatic young patients [ 3 , 14 ]. In the present study, however, COVID-19 patients during the second wave of the pandemic were slightly but significantly older than those infected during the first wave (68.26 vs. 64.52, p = 0.005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average age of the infected population is now believed to be lower compared to the pandemic outbreak in March 2020, possibly due to wider RT-PCR availability and the consequent reduction in missed diagnoses, especially in mild and asymptomatic young patients [ 3 , 14 ]. In the present study, however, COVID-19 patients during the second wave of the pandemic were slightly but significantly older than those infected during the first wave (68.26 vs. 64.52, p = 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…These measures have been effective in slowing down the pandemic, possibly reducing many millions of infections and averting the deaths of millions more; thus, they have been adopted as a model by many other countries. Moreover, several studies [ 2 ] have claimed that the seasonality of the immune response and the germicidal properties of solar UV rays during the summer months of 2020, as well as improved air quality due to city lockdowns [ 3 ], could have contributed to mitigating the COVID-19 epidemic, with a consequent reduction in both infection rate and criticality.…”
Section: Purposementioning
confidence: 99%
“…The International Committee on Taxonomy of viruses grouped into two genotypes: European (Type 1, Lelystad) and North American (Type 2, VR-2332). Nowadays, multiple genetic lineages coexist in Chinese swine herds, including lineage 1 (NADC30-like), 3 (QYYZ-like), 5 (VR2332-like), and 8 ((CH-1a-Like/JXA1-like) of type 2 PRRSV [8,9]. As RNA-dependent RNA polymerase (RdRp) lacks the 3 to 5 proofreading exonuclease activity, considerable genetic heterogeneity and taxonomic diversity have been noted among the PRRSV strains fully sequenced to date.…”
Section: Introductionmentioning
confidence: 99%
“…After 2006, HP-PRRSV strains become the predominant epidemic strains on pig farms (12). Since 2014, NADC30-like strains gradually increased in dominancy from HP-PRRS and became the most prevalent strains in mainland China (13,14). Liu et al (14) reported that from 2017 to 2019, 39 out of 62 PRRS positive fecal swabs were the NADC30-like strain.…”
Section: Introductionmentioning
confidence: 99%